Entre os muros da escola: o saber experiencial emergente nas aulas de educação física da periferia - Borges, Camila [UNESP]; Hunger, Dagmar Aparecida Cynthia França [UNESP] (My University, 2014)
This study aimed to analyze the teachers´ knowledge of a physical education teacher network state of São Paulo. The interviewed reported having problems regarding the use of the court, especially because there is invasion of the community to smoking marijuana and/ou playing football, revealing the predominance of experiential knowledge to work in a new school, whose location and local culture do not seem to prioritize this social space as learning, dissemination and preservation of other bodily manifestations of the process of human civilization. It was found in such a setting an imbalance of the relative strengths of power between teacher and students, from schools, football and drugs in relation to body movement culture, it being understood that the relationships between these individuals are interdependent and dynamic. Finally, it urges an integrated process in educational, family, social and political fields from the perspective of balancing forces in relation to the use of that space, providing conditions for teaching and propagation of content (games, sports, gymnastics, dances and fights) of the body movement culture.

Este estudio tuvo como objetivo analizar el conocimiento de profesores de una maestra de educación física de la red del estado de São Paulo. La profesora entrevistada informó tener problemas para la utilización de la cancha, sobre todo porque hay invasión de la comunidad para fumar marihuana y/o jugar la pelota, revelando el predominio del conocimiento de la experiencia para trabajar en una nueva escuela, cuya ubicación y la cultura local no parecen dar prioridad a este espacio social como aprendizaje, difusión y preservación de otras manifestaciones físicas del proceso de la civilización humana. Fue encontrado en esa configuración un desequilibrio de las fuerzas relativas de poder entre el profesor y los estudiantes, de la escuela, del fútbol y de las drogas en relación con la cultura corporal del movimiento, en la comprensión de que las relaciones entre estos individuos son interdependientes y dinámicas. Por último, insta un proceso integrado en los ámbitos educativo, familiar, social y político desde la perspectiva del equilibrio de fuerzas en relación con el uso de ese espacio, proporcionando las condiciones para la enseñanza y difusión de contenido (juegos, deportes, gimnasia, danzas y luchas) de la cultura corporal del movimiento.

Este estudo objetivou analisar os saberes docentes de uma professora de Educação Física da rede estadual de São Paulo. A professora entrevistada relatou que tem problemas quanto ao uso da quadra, em especial porque há invasão da comunidade para o uso de entorpecentes e/ou jogar apenas o futebol, revelando a predominância dos saberes experienciais para atuar numa escola nova, cuja localização e cultura local parecem não priorizar este espaço social como aprendizagem, disseminação e preservação das demais manifestações corporais do processo da civilização humana. Constatou-se em tal configuração um desequilíbrio das forças relativas de poderes entre professora e alunos, do mundo escolar, do futebol e das drogas em relação à cultura corporal de movimento, compreendendo-se que as relações entre esses indivíduos são interdependentes e dinâmicas. Enfim, urge um processo integrado nos campos educacional, familiar, social e político na perspectiva de se equilibrar as forças no que se refere ao uso desse espaço, propiciando condições para o ensino e a propagação dos conteúdos (jogos, esportes, ginásticas, danças e lutas) da cultura corporal de movimento.
Among the school walls: The emerging experiential knowledge in physical education clases in the periphery
Entre las paredes de la escuela: El conocimiento de la experiencia emergente en las clases de educación física en la periferia
Keywords: School physical education; Teachers´ knowledge; Relative strengths of power; Norbert Elias; Educación física escolar; Conocimiento de profesores; Fuerzas relativas de poder; Norbert Elias; Educação Física escolar; Saberes docentes; Forças relativas de poder; Norbert Elias